Fostering inclusive learning environments through culturally responsive pedagogy for international students in U.S. higher education - Bi, Xiaoqian (Journal of International Students, 2025)
When international students study at United States higher education institutions, they often encounter challenges that impact acculturation and academic success. This study applied community-based research to explore these students’ experiences and discuss solutions in the form of culturally responsive pedagogy (CRP). I conducted semi-structured interviews with five international students in a Curriculum and Instruction graduate program at a Western U.S. university. Some participants reflected on opportunities they have had for diverse learning expressions and external support, but they also reported obstacles, such as some professors who use materials that are only relevant to American students. This research concluded that often, when professors are open-minded and culturally sensitive, students can become more engaged in the classroom, increase academic performance, and develop a healthy sense of belonging. This study sought to inspire more faculty to effectively implement CRP, ultimately contributing to more caring and inclusive learning environments for international students.